ANALISA DESAIN UI/UX WEBSITE E-LEARNINGMTSN 33 JAKARTA MENGGUNAKAN METODE USER CENTERED DESIGN - Putra, Aleandra; Kristiana, Titin (Jurnal Ilmiah Sistem Informasi, 2025)
This study aims to evaluate and improve the user interface (UI/UX) design of the e-learning platform at MTsN 33 Jakarta using the User Centered Design (UCD) method. This method is applied to identify user needs and preferences through observation, interviews, and questionnaires, and to generate design solutions focused on comfort and ease of use. The development process begins with the creation of a wireframe (low-fidelity prototype), followed by the creation of a high-fidelity prototype using Figma software. Evaluation is conducted using the System Usability Scale (SUS) to measure the usability of the system, comparing the old system and the new design. The analysis results show that the old design has an average SUS score of 48.71, categorized as "Not Acceptable" with a "Poor" rating, while the new design achieved a score of 82.00, categorized as "Acceptable" with an "Excellent" rating. These findings indicate that the application of UCD successfully improved usability and user experience, contributing significantly to the development of a more intuitive and responsive e-learning system that meets user needs.